Penerapan Metode Outdoor Study pada Muatan IPA untuk Meningkatkan Kemampuan Kognitif Siswa Kelas V Sekolah Dasar - Renita Nuraini; Faizal Chan; Violita Zahyuni (Journal on Education, 2023)
The learning process will be more meaningful if it applies learning that can be a place for students to be able to improve cognitive abilities. This research is motivated by a problem, namely the low cognitive abilities of students in the science learning content of fifth grade students at SDN 14/I Sungai Baung. This is evidenced by the acquisition of a class average of 48 and still below the school completeness criteria. Therefore, the purpose of this research is to describe how the application of the outdoor study method to science content can improve the cognitive abilities of fifth grade students at SDN 14/I Sungai Baung. This research was conducted at SDN 14/I Sungai Baung in the even semester of the 2022/2023 academic year. This type of research is classroom action research, which consists of II cycles with research procedures carried out through 4 stages, namely planning, implementing, observing, and reflecting. The subjects of this study were fifth grade students at SDN 14/I Sungai Baung. Data collection techniques in this study were tests and observations. The results showed that by applying the outdoor study method to the science learning content of fifth grade students was able to improve students' cognitive abilities. This can be seen in the increase in student learning activities and this increase can be seen in the data analysis of each meeting cycle, namely the results of the initial test obtained the percentage of learning completeness, namely 28.6% with an average value of 50. In cycle I, the percentage of student learning completeness was obtained increased to 66.7% with an average value of 69.28. In cycle II the percentage of student learning completeness increased again to 95.2% with an average value of 80.05